De Lima laments SC ruling, hits 'Dutertism' (Philippine Daily Inquirer, 2017)
De Lima lamented the SC ruling that rejected her petition to dismiss the charges brought against her by the Duterte administration, which she said showed the extent to which "Dutertism" had distorted reason and suppressed the truth in the government and legalized the political persecution of dissenters in the country.